2001
DOI: 10.1021/ie000432i
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of FeMoNi Ternary Sulfide Supported on a Nanoparticulate Carbon in the Liquefaction of Indonesian Coals

Abstract: A series of ternary sulfide catalysts of Fe, Mo, and Ni supported on a nanoparticulate carbon, Ketjen Black (KB), have been shown to be as active as sulfided Mo and Ni catalysts containing significantly greater quantities of Mo for the liquefaction of some Indonesian coals. Thus, it is possible to retain a high catalytic activity when replacing some expensive Mo by cheap Fe. Under the reaction conditions of 450 °C and 15 MPa of H 2 pressure at solvent (tetralin)/coal/catalyst weight ratios of 1/1/0.03, FeMoNi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Nevertheless, it is expensive and limited in quantity, leading to finding alternatives to reach cost-effective production, that is, non-noble metal catalysts. Among the non-noble metal sources, activated carbon is majorly used as support since it has a high surface area, performs as a reinforcing site for the active metal sites, and can chemically absorb the reactants due to consisting of various functional groups on its surface, either having acidic or basic characteristics 5,13,14) . Activated carbon has also been successfully made into composites as a gasoline absorbent agent 15) .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is expensive and limited in quantity, leading to finding alternatives to reach cost-effective production, that is, non-noble metal catalysts. Among the non-noble metal sources, activated carbon is majorly used as support since it has a high surface area, performs as a reinforcing site for the active metal sites, and can chemically absorb the reactants due to consisting of various functional groups on its surface, either having acidic or basic characteristics 5,13,14) . Activated carbon has also been successfully made into composites as a gasoline absorbent agent 15) .…”
Section: Introductionmentioning
confidence: 99%
“…A catalyst useful in DCL should promote hydrogenation, cracking, hydrocracking and the removal of heteroatoms reactions. The catalysts most used in the DCL are iron sulfides due to its low cost although its activity is not the highest [4]. From the studies carried out with bulk catalysts, catalysts impregnated directly on the coal to be liquefied and supported catalysts [5,6,7], it is inferred that, the latter are preferred because they are suitable for hydrogenating the coal, reduce operating costs, increase the dispersion of the active phase and some supports allow the recovery of the metal; however, they are rapidly deactivated by deposition of carbonaceous material on the active phase [3].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the synergy between nickel and molybdenum sulfides was also proposed as realizable in residue slurry hydroconversion due to the interaction between weakly stacked MoS 2 slabs and the nanoparticles of Ni 3 S 2 acting as supports . Several studies indicated that the incorporation of iron to molybdenum, cobalt, vanadium, and nickel, is relatively easy. , However, the synergetic effects between iron and the second metal on hydrodesulfurization activity were not remarkable. , As for the coal liquefaction performance, Fe–Ni sulfides produced similar hydrogenation activity to the Ni–Mo sulfides for the coal liquefaction with tetralin, reaching a high oil yield of around 70%; , the order of metal impregnation is known to influence the activity of the catalyst. , FeNi-S/γ-Al 2 O 3 facilitated the formation of active hydrogen atoms as well as further subsequent radical hydrogen transfers, and thus more organic matter in the bituminous coal was converted into a soluble portion through catalytic hydroconversion . Recently, we showed that oil-soluble Fe–Ni catalyst precursors exhibit a significant effect on the inhibition of coke formation during the co-processing of coal and heavy oil .…”
Section: Introductionmentioning
confidence: 99%
“…24,25 As for the coal liquefaction performance, Fe−Ni sulfides produced similar hydrogenation activity to the Ni−Mo sulfides for the coal liquefaction with tetralin, reaching a high oil yield of around 70%; 26,27 the order of metal impregnation is known to influence the activity of the catalyst. 28,29 FeNi-S/γ-Al 2 O 3 facilitated the formation of active hydrogen atoms as well as further subsequent radical hydrogen transfers, and thus more organic matter in the bituminous coal was converted into a soluble portion through catalytic hydroconversion. 30 Recently, we showed that oil-soluble Fe− Ni catalyst precursors exhibit a significant effect on the inhibition of coke formation during the co-processing of coal and heavy oil.…”
Section: Introductionmentioning
confidence: 99%